Evaluasi Pelaksanaan Program Desa Budaya di Argomulyo, Kapanewon Cangkringan, Kabupaten Sleman - Pratama, Rio Aditya; Suryani, Dewi Amanatun (Universitas Muhammadiyah Sumatera Utara, 2024)
This study aims to determine the implementation of the Cultural Village program in Argomulyo, Kapanewon Cangkringan, Sleman Regency and to identify the factors that support and hinder the evaluation of the CIPP. This research technique was qualitative and descriptive. The data was collected using interviews, observation, and documentation. Overall, the CIPP evaluation assessment obtained quite favorable results. Community awareness, community participation, an abundance of cultural potential, strong mutual cooperation values, natural resource potential, and strong commitment and support from both the regional and subdistrict administrations are factors that aid in the implementation of the program. While the inhibiting factors include a lack of coordination and regular meetings, limited expertise of assistants, a lack of media development, a lack of adjustments to the schedule of training and mentoring activities, a lack of network and budget, and a lack of media development. This study encourages inquiry on the effectiveness of the management of the cultural village program.Keywords: CIPP, Cultural Village, Program Evaluation, Public Policy